Peran Badan Kesatuan Bangsa Dan Politik dalam Pelaksanaan Seleksi Calon Pasukan Pengibar Bendera Pusaka Kabupaten Semarang - Alif Wulan Romandani; Shella Kartika Dewi; Nila Zulfiyani; Syifa Khoirul Ummah; Margi Wahono (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
Strengthening nationalism among the younger generation has become an important issue amid the rapid development of globalization and information technology, making the Flag Raising Troop (Pasukan Pengibar Bendera Pusaka or Paskibraka) Program a strategic medium for instilling Pancasila values and national insight. This study aims to analyze the role of National Unity and Political Agency in Semarang Regency (Badan Kesatuan Bangsa dan Politik or Bakesbangpol) in the implementation of the selection process for the Flag Raising Troop Candidates (Calon Pasukan Pengibar Bendera Pusaka or Capaska) at the regency level. This research employed a qualitative method with data collected through observation, interviews, and documentation, which were analyzed using Soerjono Soekanto’s role theory. The findings reveal that Bakesbangpol of Semarang Regency serves as the primary coordinator in the Capaska selection process, covering recruitment, selection, education and training, as well as the development of Pancasila ideology, while also facing challenges related to participants’ physical and mental readiness, strengthening youth nationalism, digitalization of the selection system, limited personnel, budget constraints, cross-sectoral coordination, and technical issues within the digital system. Therefore, strengthening institutional capacity, optimizing partnerships, enhancing coordination, and developing supporting systems are necessary to reinforce the role of Bakesbangpol in implementing an effective, transparent, and accountable Capaska selection process aimed at fostering a younger generation with strong Pancasila values and national character.